Waist circumference is associated with carotid intima media thickness in peritoneal dialysis patients - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER, 2013)
Atherosclerosis is responsible for the high mortality rate in end-stage renal disease patients. Defining risk factors for atherosclerosis may lead to reduction in cardiovascular disease through modification of these factors. Peritoneal dialysis (PD) patients are subjected to high glucose loads on a daily basis, which results in considerable weight gain and an increase in waist circumference (WC). WC as an indicator of abdominal obesity is a risk factor for atherosclerosis in the general population. Carotid artery intima media thickness (CIMT) measurement is a reliable method for the detection of early atherosclerosis. The aim of this study was to investigate the relationship between WC and CIMT and to define risk factors associated with CIMT in PD patients. Fifty-five PD patients and 40 healthy controls were included. Atherosclerosis was assessed using measurement of CIMT. Fasting blood was collected for analysis. Anthropometric parameters (age, weight, BMI, and WC) were measured. Peritoneal dialysis patients had higher WC (93.9 +/- A 1.7 vs. 87.3 +/- A 1.2 cm, p < 0.05) and CIMT (0.70 +/- A 0.02 vs. 0.57 +/- A 0.01 mm, p < 0.01) than the control group. On univariate analysis, age, WC, plaque formation, and D/P creatinine were positively correlated with CIMT, whereas residual renal function, albumin, ultrafiltration volume, and D/D0 glucose were negatively correlated. On multivariate analysis, only age, WC, and plaque formation showed correlation (p < 0.001). Carotid artery intima media thickness is associated with age, plaque formation, and WC in PD patients. WC measurement is a simple, inexpensive, reproducible, and reliable method of evaluating atherosclerosis risk in PD patients and should be assessed at every visit. Appropriate counsel should be provided to patients with greater WC who are deemed to be at risk for atherosclerosis.
Keywords: Atherosclerosis; Carotid intima media thickness; Peritoneal dialysis; Waist circumference; C-REACTIVE PROTEIN; VISCERAL FAT; RISK-FACTORS; CORONARY; DISEASE; ATHEROSCLEROSIS; COMMON; HOMOCYSTEINE; MORTALITY; PLAQUE